Effect of irradiation and thermo-induced processes on reactor in vessel elements during long-term operation - Breslavsky, D.; Tatarinova, O.; Kalchenko, O.; Tolstolutska, G. (Вопросы атомной науки и техники, 2022)
A method for determining the effect of inhomogeneous temperature distribution, irradiation damage, irradiation swelling, irradiation creep of the material on the long-term strength of reactor in vessel internals and their deformation has been developed. The deformed state of the WWER type nuclear reactor baffle was determined. Constitutive equations taking into account the hidden damage of the material are proposed. According to the results of computer simulations, the strain fields of the section of the baffle during its operation for 60 years were analyzed, the place of possible occurrence of a macroscopic defect was determined.